The Geologic Record of Two Proterozoic Supercontinents within the Belt Basin Region of Western North America - Brennan, Daniel (Curtin University, 2022)
The cyclical amalgamation and dispersal of Earth’s continents, a process known as the supercontinent cycle, provided the first-order control on the distribution of Earth resources. This Ph.D. study utilizes U/Pb geochronology (zircon, monazite, apatite), zircon isotopic data (Lu/Hf, O-), and metapelite phase equilibria modelling to establish magmatic, stratigraphic and metamorphic records in the Belt basin region of western North America and refine tectonic models of the first supercontinent Nuna and its predecessor Rodinia.